Leaf Morphological Characteristics and Biomass Distribution of Oil Palm Seedlings in the Application of Oil Palm Empty Fruit Bunches (EFB) and Watering Intervals in the Pre-Nursery - Puan Habibah; Nisa Azzahra Gusviani; Zafitra Zafitra; Enriski Efrata; Freddy Alexander Simatupang; Rizki Al Khairi Barus (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2026)
The pre-nursery stage represents an initial phase that strongly influences the subsequent quality of oil palm seedlings. Nevertheless, information regarding leaf morphology and biomass distribution of oil palm seedlings under organic fertilization and water management remains limited. This study aimed to evaluate leaf morphological traits and biomass allocation of oil palm seedlings in response to oil palm empty fruit bunch (EFB) compost application and different watering intervals during the pre-nursery stage. The experiment was arranged in a completely randomized design with two factors and three replications, consisting of EFB compost rates and watering intervals. Observed variables included leaf area, leaf number, dry weight of leaves, stems, and roots, as well as shoot–root ratio. Data were analyzed using analysis of variance at the 5% significance level and followed by Duncan’s New Multiple Range Test when significant effects occurred. The results indicated no interaction between EFB compost application and watering intervals for all observed parameters. Individually, both treatments did not significantly affect leaf morphology or biomass distribution. However, a numerical tendency of increased plant biomass was observed up to an EFB compost rate of 225 g per polybag, suggesting that seedling responses during the pre-nursery stage develop gradually rather than immediately